Peningkatan Minat Dan Hasil Belajar Matematika Melalui Strategi Example Non Example Siswa Kelas V Di SDN 01 Jatiwarno Jatipuro Karanganyar Tahun Pelajaran 2015/2016 - IRAWAN, RIKI, Dra. Risminawati, M.Pd (2016)
The purpose of this study is (1) To increase interest in learning mathematics through example non-example strategy fifth grade students of SD Negeri 01 Jatiwarno Jatipuro Karanganyar 2015/2016 Academic Year. (2) To improve mathematics learning through example non-example strategy fifth grade students of SD Negeri 01 Jatiwarno Jatipuro Karanganyar 2015/2016 Academic Year. This type of research is the Classroom Action Research (PTK). This research was done in class V SD Negeri 01 Jatiwarno in the hamlet Wates, Jatipuro, Karanganyar. The subjects of this study were teachers and students of class V SD Negeri 01 Jatiwarno, District Jatipuro, Karanganyar. The technique of collecting data using interviews, observation, documentation, and testing. Data analysis technique used is the technique of interactive analysis. The results of this study indicate that through the example of non example learning strategies proven to increase interest in math classes and learning outcomes V. Increased student interest in learning from the pre cycle of 40%. At this stage of the first cycle to 73%. At this stage of the second cycle to 85%. Improved learning outcomes indicated by the rising average value of student learning from pre-cycle 42%. At this stage of the first cycle to 67%. At this stage of the second cycle to 100%. Based on these descriptions, it can be concluded that with the example of non example through strategies to improve learning outcomes in math class V students of SD Negeri 01 Jatiwarno Jatipuro Karanganyar. Keywords: interest, learning outcomes, example non-example